Dermatomyositis. Diagnostic and therapeutic recommendations of the Polish Dermatological Society - Reich, Adam; Lis-Święty, Anna; Krasowska, Dorota; Maj, Joanna; Narbutt, Joanna; Sysa-Jedrzejowska, Anna; Wojas-Pelc, Anna; Woźniacka, Anna; Rudnicka, Lidia (Dermatology Review/Przegląd Dermatologiczny, 2021)
Dermatomyositis is an autoimmune disease characterized by skin lesions and/or symptoms of myositis. In addition to the so-called classic dermatomyositis the following forms of dermatomyositis are distinguished based on the clinical presentation: pediatric, paraneoplastic, drug-induced and amyopathic. A number of disease-specific autoantibodies are identified in dermatomyositis (including anti-Mi2, anti-TIF1, anti-NXP2, anti-SAE or anti-MDA5), presence of which may be associated with a specific clinical phenotype. The diagnosis of the severity of muscle involvement is currently based mainly on physical examination, deviations in results of laboratory investigations, electromyographic examination and imaging examination, mainly with the use of magnetic resonance imaging. Systemic glucocorticosteroids administered as monotherapy or in combination with other immunosuppressants remain the mainstay of dermatomyositis treatment, and in the absence of satisfactory improvement, intravenous immunoglobulins are used. In addition, in case of interstitial lung disease, the use of cyclophosphamide may be necessary. The choice of a therapy, as well as the rate of dose reduction, depend on the dynamics of the disease, symptoms, diagnosed immunological disorders, as well as comorbidities and the drugs used. Each diagnostic and therapeutic decision must take into account the individual clinical data of the patient and current scientific reports.